Necrotizing mesenteric vasculitis in systemic lupus erythematosus - Lourenço, MH (2024)
Systemic lupus erythematosus (SLE) is a multisystemic autoimmune disorder which may affect the gastrointestinal system. Half of the patients with SLE experience gastrointestinal symptoms, with the most common being nausea, vomiting, anorexia, and abdominal pain. Mesenteric vasculitis is a severe and rare complication of SLE and one of the most frequent causes of severe acute abdominal pain. The authors present a case of a 57-year-old woman with SLE who was diagnosed with necrotizing mesenteric vasculitis following a urinary septic shock. The patient was treated with high-dose corticosteroid therapy and cyclophosphamide, with resolution of the clinical picture.